Competencies for first year residents – physicians’ views from medical schools with different undergraduate curricula - Fürstenberg, Sophie (BMC Med Educ, 2017)
BACKGROUND: Frameworks like the CanMEDS model depicting professional roles and specific professional activities provide guidelines for postgraduate education. When medical graduates start their residency, they should possess certain competencies related to communication, management and professionalism while other competencies will be refined during postgraduate training. Our study aimed to evaluate the relevance of different competencies for a first year resident required for entrustment decision from the perspective of physicians from medical faculties with different undergraduate medical curricula. METHODS: Nine hundred fifty-two surgeons and internists from three medical schools with different undergraduate medical curricula were invited to rank 25 competencies according to their relevance for first year residents. The rankings were compared between universities, specialties, physicians’ positions, and gender. RESULTS: Two hundred two physicians participated, 76 from Hamburg University, 44 from Oldenburg University, and 82 from Technical University Munich. No significant differences were found regarding the top 10 competencies relevant for first year residents between the universities. ‘Responsibility’ was the competency with the highest rank overall. Internists ranked ‘Structure, work planning and priorities’ higher while surgeons ranked ‘Verbal communication with colleagues and supervisors’ higher. Consultants evaluated ‘Active listening to patients’ more important than department directors and residents. Female physicians ranked ‘Verbal communication with colleagues and supervisors’ and ‘Structure, work planning and priorities’ significantly higher while male physicians ranked ‘Scientifically and empirically grounded method of working’ significantly higher. CONCLUSIONS: Physicians from universities with different undergraduate curricula principally agreed on the competencies relevant for first year residents. Some differences between physicians from different positions, specialties, and gender were found. These differences should be taken into account when planning competence-based postgraduate education training programs.